2013
DOI: 10.1002/bem.21789
|View full text |Cite
|
Sign up to set email alerts
|

SAR exposure from UHF RFID reader in adult, child, pregnant woman, and fetus anatomical models

Abstract: The spread of radio frequency identification (RFID) devices in ubiquitous applications without their simultaneous exposure assessment could give rise to public concerns about their potential adverse health effects. Among the various RFID system categories, the ultra high frequency (UHF) RFID systems have recently started to be widely used in many applications. This study addresses a computational exposure assessment of the electromagnetic radiation generated by a realistic UHF RFID reader, quantifying the expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 33 publications
3
30
0
Order By: Relevance
“…Only the two worst case exposure scenarios in terms of SAR levels obtained in our previous EM computation [20] were studied. These coincide, in particular, with the RFID reader ground plane of the antenna (whose characteristics are detailed in [20]) positioned:…”
Section: A Anatomical Models and Exposure Scenariomentioning
confidence: 99%
See 2 more Smart Citations
“…Only the two worst case exposure scenarios in terms of SAR levels obtained in our previous EM computation [20] were studied. These coincide, in particular, with the RFID reader ground plane of the antenna (whose characteristics are detailed in [20]) positioned:…”
Section: A Anatomical Models and Exposure Scenariomentioning
confidence: 99%
“…The models were obtained from partial deformations of the womb of the adult female model named "Ella" of the Virtual Family [21] and by integrating the segmented MRI images of pregnant women abdomens [22]. Only the two worst case exposure scenarios in terms of SAR levels obtained in our previous EM computation [20] were studied. These coincide, in particular, with the RFID reader ground plane of the antenna (whose characteristics are detailed in [20]) positioned:…”
Section: A Anatomical Models and Exposure Scenariomentioning
confidence: 99%
See 1 more Smart Citation
“…Many student tracking systems have been developed in which mostly employ radio frequency based devices. Recent studies in radiation exposure [48], [49] reported that children are more likely to be vulnerable than healthy adults to radio frequency electromagnetic radiation. So the development of children tracking system with less or no radiation based methods will reduce the risk of a child's vulnerability towards radiations which is challenging.…”
Section: Ists Challengesmentioning
confidence: 99%
“…Particular concerns regarding the minors' EMF safety evoked keen discussions on the standards' conservativeness [Gandhi and Kang, 2001;Martinéz-Búrdalo et al, 2010;Fiocchi et al, 2011a,b;Fiocchi et al, 2013]. Neonate and child models age of 5 or older were used in the studies.…”
mentioning
confidence: 99%